Characterization and biocontrol potential of some rhizobacteria against fungal pathogens causing foliar diseases in maize - AKANMU, Akinlolu Olalekan; BABALOLA, Olubukola Oluranti (Studia Universitatis Babeș-Bolyai Biologia, 2024)
Maize is one of the most consumed cereal crops worldwide, and it is a strategic crop to the attainment of SDG 2 of Zero hunger. Despite its importance, the cultivation of maize has been significantly impaired by fungal pathogens causing foliar diseases. The occurrence of this disease in maize plantations at the Research Farm of the North-West University, Molelwane, Mafikeng, South Africa prompted this investigation. Samples of diseased maize rhizosphere soil were aseptically collected. Bacteria species associated with the rhizosphere were isolated and characterized as Bacillus siamensis, Enterobacter asburiae, Enterobacter chengduensis, Priestia aryabhattai, Burkholderia sp., Priestia megaterium strain AOA6 and Priestia megaterium strain AOA7. The anti-fungicidal potentials of the bacterial species were evaluated against pathogenic fungal species, Nigrospora sphaerica, Alternaria alternata and Fusarium equiseti in-vitro. The percentage mycelia growths were calculated and the data were subjected to ANOVA using SAS version 9.8. All the seven bacteria isolates tested positive to ammonia production, phosphate solubilization, siderophore production and ACC deaminase tests. The percentage mycelia inhibition showed Nigrospora sphaerica (36.29%), A. alternata (26.19%) and F. equiseti (20.63%) as the order of fungal inhibition by the bacteria species. Furthermore, E. asburiae > P. megatarium strain AOA7 > B. siamensis > P. aryabhattai > E. chengduensis > Bulkholderia sp. were the order of antifungal efficacy of the bacteria species evaluated. In conclusion, the efficacy of the bacteria especially E. asburiae, P. megatarium strain AOA7 and B. siamensis over various fungal pathogens. The result obtained, therefore, justifies the further investigation, formulation and deployment of the bacteria species as biofungicide in the management of foliar diseases of maize. Article history: Received 27 January 2024; Revised 29 March 2024; Accepted 10 May 2024; Available online 30 June 2024.